A three-dimensional Au nanoparticle–monolayer graphene–Ag hexagon nanoarray structure for high-performance surface-enhanced Raman scattering. Issue 20 (17th February 2017) - Zhao, Yuan; Zhao, Shasha; Zhang, Lichun; Liu, Yu; Li, Xiyu; Lu, Yalin
Abstract : The three-dimensional Au nanoparticle–monolayer graphene–Ag hexagon nanoarray structure exhibits 3107-fold enhancement of the Raman response of graphene and high-performance SERS sensing. Abstract : Integration of graphene with plasmonic metal nanoparticles (NPs) holds great promise for constructing high-performance surface-enhanced Raman scattering (SERS) substrates. Here, we fabricate an artificial three-dimensional (3D) SERS substrate by assembling Au NPs on graphene supported with electron beam lithography-fabricated Ag hexagon nanoarrays (HNAs). Through modulation of the structures to sufficiently narrow interparticle spaces, we have created high-density sub-10 nm gaps between the horizontally patterned Ag hexagons with an excellent uniformity. Moreover, nanometer-scale gaps were formed with the successful embedding of monolayer graphene (1LG) between Au NPs and Ag HNAs. Finite element numerical simulations revealed the electric field enhancement effect for the 3D hybrid system with a maximum of 107 due to the multi-dimensional plasmonic couplings including Au NP–Au NP, Au NP–Ag hexagon and Ag hexagon–Ag hexagon couplings. By combining the SERS activity and high order of Ag HNAs, the chemical stability of Au, and the single-atomic thickness of graphene, the fabricated 3D Au NP–1LG–Ag HNA structure exhibits a 3107-fold enhancement of the Raman response of graphene and high SERS sensitivity with a detection limit down to 0.1 pM for Rhodamine 6G molecules, as well as good reliability and stability. In addition, the 3D SERS substrate facilitated the simultaneous detection of both Rhodamine 6G and crystal violet molecules. This work represents a step towards high-performance SERS substrate fabrication, and opens a new window to the rational design of graphene–plasmonic hybrids for SERS applications.